(3EQTGO GdeQjO GdSGdc Edi ef jbJOi Hg ef EeGei GdLeGYJjf ef GdeSLO GdeMeOi Ydi ePgH GdEeGe eGdcs - (3eMeO GdZjdGfjs
(3ChdgG (B:s
(3CeG HYO CjgG GdENhGf GdeTabhf Ydi Ojfge GdeMGaXhf Ydi GdLeGYI ai GdeSLO GdTQja GdfHhi s
(3BNQgG (B:s
(3heMd JfRdGJ GdNjQGJ Cf JgH ef GdQMeGf fSeGJ GdQMeGJ Cejf JeJ HNjQ s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg eGdc (B120) s
Keywords: (3Gdabg GdeGdcjs